His sinful touch [large type] - Camp, Candace (Camp, Candace. Mad Morelands., 2018)
When a woman who only remembers her name shows up on his doorstep, bruised and in desperate need of assistance, Alexander Moreland agrees to help her solve the mystery of her past before whatever she's running from catches up to her.